Vibrational properties of germanane and fluorinated germanene in the chair, boat, and zigzag-line configurations. (2nd January 2019) - Rivera-Julio, J; González-García, A; González-Hernández, R; López-Pérez, W; Peeters, F M; Hernández-Nieves, A D
Abstract: The electronic and vibrational properties of germanane and fluorinated germanene are studied within density functional theory (DFT) and density functional perturbation theory frameworks. Different structural configurations of germanane and fluorinated germanene are investigated. The energy difference between the different configurations are consistently smaller than the energy of thermal fluctuations for all the analyzed DFT functionals LDA, GGA, and hybrid functionals, which implies that, in principle, it is possible to find these different configurations in different regions of the sample as minority phases or local defects. We calculate the Raman and infrared spectra for these configurations by using ab initio calculations and compare it with available experimental spectra for germanane. Our results show the presence of minority phases compatible with the configurations analyzed in this work. As these low energy configurations are metastable the present work shows that the synthesis of these energy competing phases is feasible by selectively changing the synthesis conditions, which is an opportunity to expand in this way the availability of new two-dimensional compounds.